Concerns arise: wheat allergy risk in pre-packaged food products from China - Wenfeng Liu; Jian Wang; Zhongliang Wang; Fangfang Min; Yong Wu; Juanli Yuan; Jinyan Gao; Hongbing Chen (Food Science and Human Wellness)
Understanding and monitoring the cross-contamination of food allergens is crucial for safeguarding public health and ensuring food safety. Food allergen risk assessment, derived from classical toxicological principles, can identify and quantify the risk of allergies. This study aimed to investigate the risk of wheat allergic reactions to prepackaged foods from China through the utilization of food allergen risk assessment. A total of 575 products have been surveyed, wheat/gluten, milk and egg were major allergens labelled on products. According to voluntary incidental trace allergen labelling 3.0 (VITAL® 3.0) program, the number of products belonged to Action Level 2 were 303. Integration of precautionary allergen labeling (PAL) analysis indicated that 9.57% products would pose a potential risk to wheat allergic individuals. The probabilistic risk assessment results suggest that 7984 allergic reactions may arise among wheat-allergic consumers during 10000 eating occasions due to the consumption of pre-packaged food products with incorrect wheat-related allergen labelling. This study demonstrated that a risk assessment-based approach can support the guidance of allergen labelling and management of food allergen for pre-packaged food products, providing protection for allergic individuals in food consumption and for food manufacturers in food production and trade.